Agatha Christe : an autobiography - Christie, Agatha (London : Harper Collins Publisher, 1977)
Dame Agatha Christie sheds light on her secretive life and tells of her early years, her marriages and rise to success.
Includes index.
Keywords: Authors, English -- Biography. -- 20th century; Authors, English